The Romanian export with livestocks-live animals: A far-reaching activity? - Mariana Grodea; Iuliana Ionel (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 6th Edition of the International Symposium, November 2015, Bucharest, 2015)
In the period 2003-2014, Romania became an important source for the export of live animals (bovines and sheep), both for the intra-Community trade and for third countries. Although in the same period the imports consisted mainly of breeding animals, the balance of trade was constantly positive. The method used in the paper was the comparative analysis of trade-specific set of indicators, the main information sources being international information, reports and studies, FAOSTAT and EUROSTAT statistics. From our analysis, it results that that Romania practiced a conjuncture export, as the herds specialized in meat production, both in the case of bovines and sheep, have a significant share in total livestock herds. The reason why Romania is agreed as supplier of live animals is rather represented by the raising of animals under extensive system, where feeding is mainly based on grazing.
Keywords: 330; import; export; bovines; sheep; balance of trade